Seasonal metabolic adjustments and partitioning of evaporative water loss in Wahlberg’s epauletted fruit bat,Epomophorus Wahlbergi - McKechnie, Andrew E. (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2013.